Pedagogical Conditions for Developing Intercultural Competence in Preservice Preschool Educators - Olena Pinzenik (Pedagogical Discourse, 2021)
The article provides theoretical substantiation to the problem related to developing intercultural competence of preservice preschool educators who will work at preschool education institutions. It defines the content of the «intercultural competence of the preservice preschool educators at preschool education institutions», its significance for the preschool educators’ professional activity.The findings are received in experimental work and explain what level of intercultural competence preservice preschool educators have. The findings indicate a lack of multicultural knowledge, which leads to difficulties in organizing and conducting classes, educational work, practice and extracurricular professional activities. To improve preservice preschool educators’ level of intercultural competence the pedagogical conditions were outlined. It states that intercultural competence of preservice preschool depends on whether the content of professional training responds to multicultural community needs; and whether the setting of the higher education institution responds to the needs of multiculturalism. The efficiency of the presented pedagogical conditions was proved and substantiated by the experimental work.